GEOLOGICAL INTERPRETATION OF THE OFFSHORE SEDIMENTARY BASIN OF NORTH CENTRAL JAVA BASED ON SPECTRAL ANALYSIS AND 2D GRAVITY MODELING - Restu Ningsih; Imam Setiadi; Riza Rahardiawan; Ordas Dewanto; Rahmi Mulyasari (BULLETIN OF THE MARINE GEOLOGY, 2022)
The offshore sedimentary basin of North Central Java is a marine basin located in the northern part of North Serayu Basin. This basin was formed through the uplift of the southern part of Central Java (Bumiayu) caused by the movement of a pair of horizontal faults. Studies of sub-basin delineation and basement configuration are rarely carried out in this basin. Therefore, the gravity method referring to subsurface-density variations was carried out to obtain this information. This research aims to delineate sedimentary basins and interpret the geological subsurface based on gravity data using spectral analysis, highpass and lowpass filters, also 2D gravity modeling. An average estimation depth to the basement in the study area of about 2.22 km was determined using spectral analysis. Qualitative analysis shows the basement-high pattern, sub-basin, and structure lineament patterns. The 2D model shows three layers consisting of the upper sedimentary layer of Tertiary-Neogene and the middle layer of Tertiary-Paleogene sediment with a density value of 2.3 gr/cc and 2.5 gr/cc, respectively. The lower layer has the highest density of 2.67 gr/cc, assumed as a granitic basement. The results of the Second Vertical Derivative (SVD) analysis on the residual anomaly cross-sectional paths indicate the presence of thrust and normal faults which can be used to assist the interpretation of fault structures in subsurface geological models. Gravity analysis of the offshore North Central Java sedimentary basin indicates the occurrence of sub-basins and geological structure patterns that considered as a potential zone for the development of the petroleum system in this area.